THE ‘RIGHT TO THE CITY’ ON VARIOUS SCALES - NOWAK, MAREK (Society Register, 2020)
The introduction to this volume pursues two aims. On the one hand, it refers to the problem of distinguishing between ‘right to the city’ initiatives and ‘urban city movements’ as phenomena embedded in different structural moments of society. On the other hand, it attempts to propose a supplement to the discussion about the aforementioned phenomena. This supplement addresses the need to take into account different scales by which the phenomena of self-organisation in the city are analysed. The article offers an example of such analysis referring to the Central European and the Polish perspectives, treating the two stories as separate to a certain extent. As it turns out, each of them offers a slightly different reasoning and different contexts for understanding the evolution of phenomena as well as separate decisive factors shaping the empowerment processes. The reader finds here references to research analysis in sociology, urban and economic history, supplementing the existing knowledge. The proposed interpretation is intended to lead to a discussion on the need to comprehend local and regional specifics in universalising studies.